Investigating the role of exosomes in medulloblastoma and their involvement in metastasis - Jackson, Hannah Kate (2017)
Medulloblastoma, the most prevalent malignant paediatric brain tumour, accounts for around 10% of all cancer-related deaths in children. Medulloblastomas frequently metastasize; over one-third of tumours are metastatic at diagnosis and almost all patients have metastases at relapse. These patients are categorised as high-/very high-risk. Currently there is no curative treatment for patients with metastatic medulloblastoma, any advancements in the underlying biology of medulloblastoma, particularly regarding their metastatic behaviour, could help to improve patient outcome. One area that remains relatively unstudied is medulloblastoma extracellular vesicles. Extracellular vesicles are a heterogeneous population of nano-sized, cell derived vesicles. They can be categorised into three main classes, exosomes, microvesicles and apoptotic bodies. Accumulating evidence indicates that exosomes play vital roles in cancer progression. They have been shown to transfer oncogenic proteins and nucleic acid cargo to recipient cells, which modulates their activity and plays a decisive role in tumorigenesis. Exosomes have been shown to promote tumour growth and progression, by enhancing tumour cell migration and invasion, drug resistance and immunosuppressive functions. In this project, a protocol was optimised for the isolation and characterisation of medulloblastoma extracellular vesicles. Success of this was validated by nanoparticle tracking analysis, electron microscopy and western blot analysis. Our data demonstrates that medulloblastoma cells secrete two distinct populations of exosomes and microvesicles, with unique size, morphology and cargo. Our data also shows that more aggressive, metastatic cell lines produce higher quantities of exosomes compared with less aggressive, non-metastatic cell lines. In the final part of the project, candidate genes of medulloblastoma metastasis, identified from the literature, were profiled in cells and their derivative extracellular vesicles.